Implementation Of Sharia Accounting In The Mudharabah Saving Program At PKH Al-Hasanah - M. Indra Mulia Nasution; Saparuddin Siregar (Enrichment : Journal of Management, 2022)
PKH Al-Hasanah is a charity business for the residents of Halongonan District in the form of a sharia financial institution and muamalah activities based on Islamic sharia. In its operational system, PKH uses sharia accounting with the aim of knowing transactions which are then followed by recording, classifying, and summarizing these transactions so as to produce financial reports that can be used for decision making, all the rules that have been set by Allah SWT to be obeyed by humans in carrying out everything. activity in the world.